Values in foreign policy investigating ideals and interests - Srinivasan, Krishnan 1937-; Mayall, James; Pulipaka, Sanjay; IG Publishing Online (Online service). (Lanham [Maryland] Rowman & Littlefield International, 2019)
"This books throws light on whether Asian values constitute a specific genre that differentiates Asia from the West and feeds into its nations' foreign policies, and whether there is a basic difference of opinion on values or merely an aspect of contemporary power politics"--Provided by publisher.
Introduction : values and foreign policy / Krishnan Srinivasan, James Mayall and Sanjay Pulipaka -- Values in European foreign policy : defending the enlightenment in troubled times / James Mayall -- Values and European foreign economic policy : ideas, institutions and interests / Fredrik Erixon -- Values in German foreign policy : how changes of course created lasting values / Amit Das Gupta -- Values in US foreign policy : "America first" meets the pro-democracy state / William J. Antholis -- Overview : reflections on values in Western foreign policy : from the liberal world order to antithetical values / Bruno Maçães -- Values in Russian foreign policy : Soviet values, revisionism and President Putin / Hari Vasudevan and Tatiana Shaumyan -- Islamic values in foreign policy : perspectives on "secular" Turkey and "Islamic" Iran / Mehmet Ozkan and Kingshuk Chatterjee -- Values in Indian foreign policy : lofty ideals give way to parochial pragmatism / Krishnan Srinivasan -- Values in Myanmar's foreign policy : neutralism, isolationism and multi-engagement / Sanjay Pulipaka and Chaw Chaw Sein -- Values in Indonesian foreign policy : independent and active doctrine / Dewi Fortuna Anwar -- Values in Chinese foreign policy : culture, leadership and diplomacy / Zhang Lihua -- Values in South Korean foreign policy : search of new identity as a "middle power" / Lee Seong-hyon -- Values in Japanese foreign policy : between "universal values" and the search for cultural pluralism / Tadashi Anno -- Overview : reflections on values in Asian foreign policy : ASEAN's three principles / Ravi Velloor.
Includes bibliographical references and index.
Keywords: Electronic books; International relations and culture; Values -- Political aspects; Values -- Political aspects -- Asia; Political culture -- Asia; East and West; Asia -- Foreign relations